PEMBELAJARAN MATEMATIKA BERMAKNA MELALUI TABEL DAN DIAGRAM BATANG: BEST PRACTICE DI KELAS III DI SEKOLAH MITRA - Jumaria, Siti; Prayogo , Tito; Anggriani, Vivi; Januar Saputra, Henry; Dhinar Putra , Eka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the best practice of mathematics learning on table and bar chart materials to strengthen numeracy literacy skills of third grade students. The background of this study was the low understanding of students in reading, interpreting, and presenting data in table and bar chart forms. The learning process used an active learning approach through observation activities, group discussions, worksheets, and contextual problem solving. This study employed a descriptive qualitative method with quantitative data support. The subjects were 22 third grade students of partner school in the 2025/2026 academic year. Data collection techniques included observation, tests, documentation, and field notes. The results showed that the implementation of meaningful and interactive learning could improve students’ understanding of data presentation concepts. The average student learning outcome increased from 67.4 in the initial assessment to 86.8 in the final assessment. The learning mastery percentage also increased from 45% to 91%. Students became more active, enthusiastic, and able to present data in the form of tables and bar charts correctly. Therefore, learning mathematics through contextual and student-centered activities can strengthen students’ numeracy literacy skills in elementary school.